Validitas dan Reliabilitas Instrumen Harga Diri untuk Dosen Perguruan Tinggi - Sunarsih Sunarsih; Pasaman Silaban; Nagian Toni (Departemen Psikologi, Universitas Negeri Padang, 2026)
This study aims to examine the validity and reliability of a self-esteem instrument developed for lecturers in private universities in Pekanbaru, Indonesia. The instrument was constructed based on Rosenberg’s self-esteem theory, encompassing two dimensions: self-competence and self-liking. A quantitative approach was employed involving 350 lecturers from several private universities in Pekanbaru selected through a random sampling technique. Content validity was evaluated by two experts using Gregory’s formula, while internal consistency reliability was analyzed using Cronbach’s Alpha through SPSS version 25. The findings indicate that the instrument achieved a content validity index of 0.8125, categorized as high validity, and a Cronbach’s Alpha coefficient of 0.756, indicating acceptable reliability. These results suggest that the instrument possesses adequate psychometric properties and can be used to assess lecturers’ self-esteem within the context of private higher education institutions in Pekanbaru. The study contributes to the development of contextual psychological measurement tools for academic professionals.